Recombinant murine granulocyte macrophage colony-stimulating factor has megakaryocyte colony-stimulating activity and augments megakaryocyte colony stimulation by interleukin 3. - Robinson, B E (1987)
Recombinant murine granulocyte macrophage colony-stimulating factor (rGM-CSF) has been produced in Escherichia coli and purified to homogeneity. GM-CSF has an established role as an in vitro regulator of granulocyte and macrophage colony formation. We have determined that rGM-CSF also has intrinsic activity as a megakaryocyte colony-stimulating factor and that rGM-CSF augments the effect of interleukin 3 (IL-3) on megakaryocyte colony formation. The dose-response curve for megakaryocyte colony induction with rGM-CSF showed plateau megakaryocyte stimulation at 9 ng/ml. When IL-3 (at a plateau dose for megakaryocyte colony induction) was added to rGM-CSF over a 0-22-ng/ml dose range, the resultant megakaryocyte colony stimulation approximated the sum of the levels of stimulation produced by either factor alone. These results establish GM-CSF as a multilineage growth factor with definite megakaryocyte colony-stimulating activity and indicate that both GM-CSF and IL-3 are important in the regulation of megakaryocytopoiesis.